Influence of Tax, Unemployment and Political Instability to Indonesia Government Expenditures 1988-2016 Period - ., Sugiartiningsih; Juny, Hesty; Oki, Ignatius; Apriliana, Tria; Ali, Muhammad (International Journal of Engineering and Technology, 2018)
This study aims to determine the effect of taxes, unemployment and political instability on Indonesian government spending. The research method used in this study is descriptive analysis method because it is to find out the third causal relationship of independent variables on Indonesian government expenditure. The model is built multiple regression with secondary data boundaries from 1988 to 2016. Based on the results of calculations, the results of a positive relationship between tax and political instability of Indonesian government expenditure are obtained. While, unemployment has a negative relationship to Indonesian government spending. The main factor is the condition of Indonesian unemployment is high, starting from junior high school, vocational high school and even university level. While the government is trying to overcome it, it has not been optimally because of the obstacles in the village and in the city. On the contrary, tax and strong political instability after the reform of Indonesian government spending.Â Â